Using Service Blueprints to Visualize Pharmacy Innovations - David A. Holdford (MDPI AG, 2019)
Background: Applying the principles of service design can help pharmacists manage both the quality and patient perceptions of the services they provide. Service blueprints are a widely used service design tool that are rare in the healthcare literature. They can be used to design new services or revisit the design of established services. This paper describes service blueprints and their uses, and illustrates how to build one using an example. Methods: A blueprint is built for appointment-based medication synchronization services to illustrate the tool. Conclusions: Service blueprints permit pharmacists to better see and understand service processes. They clarify the process of service delivery and the roles of customers, service providers, and supporting services. They provide a way of depicting complex services in a concise visual way that communicates details at a glance. Pharmacists who utilize service blueprints can improve the consistency and quality of services provided, and they can increase the chance that every interaction with patients sends a positive message about the value of pharmacist services.